(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This thesis analyzes the influence of social media on the vocabulary of English-speaking youth. The study examines new lexical units, abbreviations, slang expressions, and internet-based language forms that emerge in young people’s speech through digital platforms such as Instagram, TikTok, Facebook, and other social networks. It also highlights how social media strengthens informal communication styles, encourages the active use of neologisms among young users, and affects the lexical structure of modern English. The thesis evaluates the role of virtual communication in the development of youth language and speech culture from a linguistic perspective.